Reduced expression of uroplakin 1A is associated with the poor prognosis of gastric adenocarcinoma patients. - Yan Zheng; Dan-dan Wang; Wei Wang; Ke Pan; Chun-yu Huang; Yuan-fang Li; Qi-jing Wang; Shu-qiang Yuan; Shan-shan Jiang; Hai-bo Qiu; Yong-ming Chen; Xiao-fei Zhang; et al. (PLoS ONE)
Background The aim of this study was to investigate the expression and prognostic significance of Uroplakin1A (UPK1A) in gastric adenocarcinoma patients. Functional studies were also analyzed in vitro. Methodology/principal findings Real-time quantitative PCR (RT-qPCR), western blotting, and immunohistochemical (IHC) staining methods were used to analyze the expression of UPK1A in primary gastric adenocarcinoma tissue samples. Compared with matched adjacent non-tumor, the expression of UPK1A in fresh surgical specimens was reduced, which was confirmed by RT-qPCR (P<0.01) and western blotting analysis (P<0.01). The paraffin specimens from a consecutive series of 445 gastric adenocarcinoma patients who underwent surgery between 2003 and 2006 were analyzed by IHC staining. The relationship between UPK1A expression, clinicopathological factors, and survival were evaluated. IHC staining analysis revealed that the reduced expression of UPK1A was observed in 224 cases (50.3%). Additionally, the correlation analysis of clinicopathological factors demonstrated that reduced expression of UPK1A was significantly associated with histological grade (P = 0.022), node metastasis (P<0.001) and tumor node metastasis (TNM) stage (P = 0.008) (7th edition of the International Union Against Cancer (UICC)). Furthermore, Kaplan-Meier survival analysis revealed that the reduced expression of UPK1A was significantly associated with poor prognosis (P = 0.043). Cox hazards model analysis indicated that UPK1A expression was an independent risk factor at the 0.1 level (P = 0.094). The function of UPK1A in cell cycle, migration, and invasion was investigated by overexpressing UPK1A in the MKN45 gastric cancer cell line. The elevated expression of UPK1A cells induced G1 phase arrest and significantly inhibited migration and invasion. Conclusions/significance The reduced expression of UPK1A might play a role in the progression of gastric cancer. Thus, UPK1A could be a potential favorable biomarker associated with gastric cancer prognosis.